2016
DOI: 10.1038/srep22320
|View full text |Cite
|
Sign up to set email alerts
|

Internal dynamics of intense twin beams and their coherence

Abstract: The dynamics of intense twin beams in pump-depleted parametric down-conversion is studied. A generalized parametric approximation is suggested to solve the quantum model. Its comparison with a semiclassical model valid for larger twin-beam intensities confirms its applicability. The experimentally observed maxima in the spectral and spatial intensity auto- and cross- correlation functions depending on pump power are explained in terms of different speeds of the (back-) flow of energy between the individual dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…This first issue is addressed by considering that the medium interacts with a twin beam composed by a larger number of entangled photon pairs and generated by means of intense parametric down-conversion (PDC) [27,28,29]. Indeed, properties of such twin beams have been commonly investigated [30,31,32] and, more importantly, it has been shown that strong quantum frequency correlations inside the twin beam persist even at these higher photon-flux conditions as shown in [33] and also later in [34,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…This first issue is addressed by considering that the medium interacts with a twin beam composed by a larger number of entangled photon pairs and generated by means of intense parametric down-conversion (PDC) [27,28,29]. Indeed, properties of such twin beams have been commonly investigated [30,31,32] and, more importantly, it has been shown that strong quantum frequency correlations inside the twin beam persist even at these higher photon-flux conditions as shown in [33] and also later in [34,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Before concluding this section, it is important to remark that although the theoretical model described above is valid for most experimental setups and applications, one most keep in mind that, as any model, it has its limitations; particularly when extremely high photon fluxes are considered [41,46,49].…”
Section: Generation Of Intense Twin Beamsmentioning
confidence: 99%
“…With the advent of ultrahigh flux sources of entangled photons [32][33][34][35][36][37], one naturally wonders whether VSS can benefit from them, especially because it has been shown that strong frequency correlations between entangled beams persist at high photon-flux conditions [38][39][40][41]. Consequently, in this paper, we provide a thorough analysis of VSS when implemented with intense entangled fields (further twin beams).…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used parametric approximation [20] considers a strong un-depleted classical pump field, which linearizes the Heisenberg equations (3). However, it fails in the regime with pump depletion, in which the so-called generalized parametric approximation [42,43] allows to find an appropriate solution. In its framework, the following linear operator equations are derived:…”
Section: Quantum Model Of Twin Beams With Coherent Componentsmentioning
confidence: 99%